Habits of televiewing in relation to certain variables - Cumba, Trinidad Soledad 1936- (s.n.], 1970)
The purpose of the study is to identify the effects of television on some grade school children of Balara Elementary School, Quezon City. The study intends to serve as a ready reference for educators and parents concerning the influence of television on the home activities of children who view television in the Balara Elementary School, specifically, their study habits, eating habits, sleeping habits, radio listening habits, movie going, and play habits.